2008
DOI: 10.1002/pssc.200776837
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical characterization of single‐phase CuIn(Se,S)2 thin films deposited using a two‐step process

Abstract: CuInSe2 has a band gap of about 1.0 eV, which limits the conversion efficiency of complete CuInSe2/CdS/ZnO devices. In order to increase the conversion efficiency of devices, it is necessary to increase the band gap value of the absorber films to about 1.2 eV. This can be achieved by systematically substituting some indium with a group III element and/or selenium with another group VI elements. The substitution of In and/or Se results in a shrinkage of the lattice parameters and thus an increase in the band ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…As can be seen, both spectra show similar spectral behavior across the observed wavelength range, with Mors presenting 1.5 times the flux of Somnus at 1.21 µm, corresponding to a difference of 0.44 mag between the components at this wavelength. Sheppard et al (2012) and Sheppard & Trujillo (2008) found a maximum difference of 0.3 mag between this pair and a mean difference of 0.1 mag.…”
Section: Mors and Somnusmentioning
confidence: 73%
“…As can be seen, both spectra show similar spectral behavior across the observed wavelength range, with Mors presenting 1.5 times the flux of Somnus at 1.21 µm, corresponding to a difference of 0.44 mag between the components at this wavelength. Sheppard et al (2012) and Sheppard & Trujillo (2008) found a maximum difference of 0.3 mag between this pair and a mean difference of 0.1 mag.…”
Section: Mors and Somnusmentioning
confidence: 73%